2021
DOI: 10.1038/s41467-021-26101-5
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal phages and pathogenicity islands drive plasmid evolution

Abstract: Conjugation has classically been considered the main mechanism driving plasmid transfer in nature. Yet bacteria frequently carry so-called non-transmissible plasmids, raising questions about how these plasmids spread. Interestingly, the size of many mobilisable and non-transmissible plasmids coincides with the average size of phages (~40 kb) or that of a family of pathogenicity islands, the phage-inducible chromosomal islands (PICIs, ~11 kb). Here, we show that phages and PICIs from Staphylococcus aureus can m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 58 publications
(71 reference statements)
2
30
0
Order By: Relevance
“…Alternatively, it has been suggested that nonconjugative plasmids in Staphylococcus spp. could be mobilized in trans by conjugative plasmids ( Ramsay et al 2016 ) or by transduction ( Humphrey et al 2021 ). Also, it was previously observed that ICEs are much more frequent than conjugative plasmids in these clades ( Guglielmini et al 2011 ), and these pMOBs might be mobilized by ICEs.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, it has been suggested that nonconjugative plasmids in Staphylococcus spp. could be mobilized in trans by conjugative plasmids ( Ramsay et al 2016 ) or by transduction ( Humphrey et al 2021 ). Also, it was previously observed that ICEs are much more frequent than conjugative plasmids in these clades ( Guglielmini et al 2011 ), and these pMOBs might be mobilized by ICEs.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that the higher number of DE genes in strain Newman could be an emergent property off competition between phage K and the resident prophages. Chen et al ( 45 ) showed that the induced pac -type phages φNM1, φNM2, and φNM4 of strain Newman facilitate amplification of the host DNA flanking the prophage, which could lead to horizontal gene transfer by lateral transduction ( 46 , 47 ). Moreover, the temperate phages play a key role in the spread of the SaPIs ( 48 , 49 ) and the generalized transduction of other mobile genetic elements ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among E. coli plasmids, there are 7% of phage-plasmids that can transfer within their own viral particles. In S. aureus, phage-plasmids are rare, but plasmids can be transduced by phages and their satellites 47 . Phages and satellites can transduce pieces of DNA of approximately the size of their own genomes.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the genomes of temperate phages matches the largest mode of the sizes of pMOBless and the size of the satellite genomes matches the smallest mode of these plasmids. It was proposed that plasmids were selected to have sizes compatible with transduction by phages and satellites, which explains the bimodal distribution of plasmid sizes (Fig 7B) 47 . If correct, transduction by phages and their satellites would explain the enigmatic bi-modality of plasmid sizes, while gene deletions causing the transitions between pCONJ or pMOB to pOriT would explain why the latter tend to follow the size distribution of the former.…”
Section: Discussionmentioning
confidence: 99%